Novelties for the vascular fl ora of Santa Fe province (Argentina). - EXNER, E. (Universidad Nacional del Litoral, 2021)
As a result of collection trips carried out in the province of Santa Fe, 13 taxa were documented for the first time for the province, 10 native and 3 introduced taxa, one of the latter representing a new report for Argentina.